Eco-friendly synthesis and characterizations of single-wall carbon nanotubes/Ag nanopaticle hybrids for environmental decontamination. (5th December 2018) - He, H-Y; He, Z; Shen, Q
Abstract: Single-wall carbon nanotubes (CNTs) functionalized by various molecules and semiconductors have provided a unique class of tunable chemistries for a variety of application. This work functionalized the CNTs with Ag nanoparticles that were in situ synthesized by using holly leaf extract as a reduction agent to achieve a photocatalyst with high photocatalytic activity. The hybrids were characterized by various techniques to understand their chemical and physical properties. The Ag nanoparticles were successfully formed and well coupled on the CNTs surface. The holly leaf extract with low reduction ability leads to a slow formation of Ag nanoparticles and so small average particle size. The formed Ag nanoparticles showed granular particle morphology with a nano-scale size of ∼7–20.3 nm. Lower Ag + concentration in the precursor solution for the hybrid with lower Ag content leads to smaller average particle size. The two photoluminescence peaks weakened with increasing Ag content, originating from the increase in average particle size. Moreover, hydroxyls existed on the surface of the hybrids exists, indicating a good surface hydrophilicity. Ag showed a efficient sensitization, making the hybrids exhibited a better photocatalytic activity than pure CNTs. Appropriate low Ag content of 5 wt% resulted in the highest activity. The Ag sensitization also enhanced the reductive photocatalysis of CNTs, resulting in further degradation of phenyl in the intermediates.